2020
DOI: 10.1109/access.2020.2966564
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of HMDs/FSDs and Gender Differences on Cognitive Processing Ability and User Experience of the Stroop Task-Embedded Virtual Reality Driving System (STEVRDS)

Abstract: The advent of virtual reality technology has provided a new approach for assessing and training cognitive processing ability, with the design of simulations used to replicate real events in everyday lives. To better understand how head mounted displays/flat screen displays (HMDs/FSDs) and differences in the individuals who use them affect cognitive performance and the use of VR systems, our research group created the Stroop task-embedded virtual reality driving system (STEVRDS) and conducted a 2 × 2 between-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In particular, the scores of mental demand and frustration were significantly different between the two systems, as users felt dizzy or mentally stressed when participating in the experiment. Chang et al [82] designed a driving system with embedded Stroop tasks. Stroop task had been used to assess cognitive processing and selective attention abilities, which asked an individual to distinguish whether a certain word's meaning and visual color match [82].…”
Section: Cognitive Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the scores of mental demand and frustration were significantly different between the two systems, as users felt dizzy or mentally stressed when participating in the experiment. Chang et al [82] designed a driving system with embedded Stroop tasks. Stroop task had been used to assess cognitive processing and selective attention abilities, which asked an individual to distinguish whether a certain word's meaning and visual color match [82].…”
Section: Cognitive Loadmentioning
confidence: 99%
“…Chang et al [82] designed a driving system with embedded Stroop tasks. Stroop task had been used to assess cognitive processing and selective attention abilities, which asked an individual to distinguish whether a certain word's meaning and visual color match [82]. They found that the average response time when users answered Stroop trials in the FSD (flat-screen displays) condition was shorter than that in the HMD condition.…”
Section: Cognitive Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HMDs usually block the view of the surrounding physical environment completely, which can further increase immersivity (see Slater, 2018). These differences can lead to higher perceived presence when using HMDs (Chang et al, 2020;Li et al, 2020;Yao & Kim, 2019) and have behavioral implications, such as greater physical effort with HMDs (Yao & Kim, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have not included any direct comparison between the platforms, although the tasks included could be implemented with small adjustments in both. However, some other studies with relatively recent HMD hardware have compared the two technologies directly by implementing the same task with both, albeit their scenarios were not taken directly from ordinary daily life (Brooks et al, 2017;Chang et al, 2020). Brooks and colleagues (2017) compared the HMD and FSD versions of a military flight simulator in a within-subjects study and found no difference in target detection performance between the two versions, but their participants reported higher mental workload and discomfort when using the HMD.…”
Section: Introductionmentioning
confidence: 99%